Extracellular cation sensing by the enterocyte: prediction of a novel divalent cation "receptor". - Pazianas, M; Adebanjo, O; Shankar, V; James, S; Colston, K; Maxwell, J; Zaidi, M (1995)
We report that the divalent cation Ni2+ elicits elevations in the cytosolic free Ca2+ concentration ([Ca2+]) in cultured enterocytes. These elevations were monophasic, each response consisting of a rapid initial transient rise of cytosolic [Ca2+] to a peak value followed by an exponential decline. The magnitude of the cytosolic [Ca2+] elevation varied with the concentration of applied Ni2+. In some cells, a single application of Ni2+ induced oscillatory changes in cytosolic [Ca2+]. There was also evidence for use-dependent inactivation: a conditioning application of Ni2+ substantially attenuated the response resulting from its subsequent application. Our findings thus demonstrate the existence of a divalent cation-sensing "receptor" on the enterocyte. This putative receptor may play a role in regulating mineral absorption across the enterocyte membrane.